A single‐point mutation (Ala280Val) in the third intracellular loop alters the signalling properties of the human histamine H3 receptor stably expressed in CHO‐K1 cells. (15th August 2013) - Flores‐Clemente, Cecilia; Osorio‐Espinoza, Angélica; Escamilla‐Sánchez, Juan; Leurs, Rob; Arias, Juan‐Manuel; Arias‐Montaño, José‐Antonio
<x xml:space="preserve">Abstract</x> Background and Purpose An alanine to valine exchange at amino acid position 280 (A280V) in the third intracellular loop of the human histamine H3 receptor was first identified in a patient suffering from Shy–Drager syndrome and later reported as a risk factor for migraine. Here, we have compared the pharmacological and signalling properties of wild‐type (hH3RWT) and A280V mutant (hH3RA280V) receptors stably expressed in CHO‐K1 cells. Experimental Approach The hH3RA280V cDNA was created by overlapping extension PCR amplification. Receptor expression and affinity were assessed by radioligand (N‐α‐[methyl‐3H]‐histamine) binding to cell membranes, and receptor function by the inhibition of forskolin‐induced cAMP accumulation and stimulation of ERK1/2 phosphorylation in intact cells, as well as stimulation of [35S]‐GTPγS binding to cell membranes. Key Results Both receptors were expressed at similar levels with no significant differences in their affinities for H3 receptor ligands. Upon activation the hH3RWT was significantly more efficacious to inhibit forskolin‐induced cAMP accumulation and to stimulate [35S]‐GTPγS binding, with no difference in pEC50 estimates. The hH3RWT was also more efficacious to stimulate ERK1/2 phosphorylation, but this difference was not significant. The inverse agonist ciproxifan was more efficacious at hH3RWT to reduce [35S]‐GTPγS binding but, for both receptors, failed to enhance forskolin‐induced cAMP accumulation. Conclusions and Implications The A280V mutation reduces the signalling efficacy of the human H3 receptor. This effect may be relevant to the pathophysiology of disorders associated with the mutation. Linked Articles This article is part of a themed issue on Histamine Pharmacology Update. To view the other articles in this issue visit http://dx.doi.org/10.1111/bph.2013.170.issue‐1